Effects of venous pressure on coronary circulation and intramyocardial fluid mechanics - Izrailtyan, I; Frasch, H F; Kresh, J Y (The American journal of physiology, 1994)
This investigation examined the interaction between right heart pressure (RHP), coronary perfusion pressure (CPP), intramyocardial tissue pressure (IMP), and coronary flow mechanics, including partitioning of coronary effluent in the isolated Krebs-Henseleit perfused rabbit heart. The major new finding was a parallel shift in the IMP-inflow relationship to a higher tissue pressure level in response to an increase in RHP. Accompanying the rise in RHP from 0 to 15 and 25 mmHg, IMP at zero coronary inflow in the beating (and arrested) heart increased from 5.8 +/- 1.0 (7.7 +/- 1.2) to 16.3 +/- 1.2 (17.9 +/- 1.3) and 28.6 +/- 1.7 (26.4 +/- 2.0) mmHg, respectively. A concomitant parallel shift in the CPP-inflow relation to higher pressures was consistently observed. The fraction of total coronary flow drained by the right heart was not constant. A higher partition of coronary outflow to the left heart (7.8 +/- 3.8, 34.3 +/- 3.0, and 47.9 +/- 4.3%, respectively) accompanied the increase in RHP. Intramyocardial partitioning of coronary outflow pathways mediates the effects of venous pressure modulation on coronary circulation. The interaction between coronary venous pressure and the extravascular environment modifies the effective back pressure to arterial inflow.